EFEKTIVITAS PELAKSANAAN PROGRAM KESEHATAN LINGKUNGAN PADA UPTD KESEHATAN KARI KABUPATEN KUANTAN SINGINGI - Ega Novita Windari; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The environment of the Indonesian population is not a good settlement, only a smallportion of the population enjoying clean water sanitation facilities. This resulted in a highrate of morbidity and mortality due the various diseases. Improved environmental health areintended to improve the quality of living environmentthat can ensure the health, throught theimprovement of basic sanitation activities as well as prevention and control of physical andbiological condition are not good, including a variety of side effects of development. As wellas environmental sanitation activities and settlements made by Health center staff UPTDshould be implemented by involving the community work together for good result. This studyaims to determine the effectiveness of implementation of the Environmental Health ProgramHealth UPTD Kari Kuantan Singingi District, and the factors that influence the effectivenessof implementation of the Environmental Health Program Health UPTD Kari KuantanSingingi District. Theory used in this study was the effectiveness of the theory put forward bysteers, program, effectiveness of program and environmental health. This study usesqualitative research methods to study descriptive data. In data collection, researchers usingobservation, interviews, documentation, and literature. By using key informan. In thequalitative descriptive data analysis found that the effectiveness of implementation of theEnvironmental Health Program Health UPTD Kari Kuantan Singingi District has not beeneffective. Can be seen from not achieving the objectives and the expected rate of change inthe program. In this study are known factors that influence the effectiveness ofimplementation of the Environmental Health Program Health UPTD Kari Kuantan SingingiDistrict, among other factors poor implementers and inadequate in terms of quality andquantity, lack of funds and socialization programs to the community that has not been goodin the implementation program.Abstrak: Efektivitas Pelaksanaan Program Kesehatan Lingkungan pada UPTDKesehatan Kari Kabupaten Kuantan Singingi